Change in Intraocular Pressure in the Fellow Eye After Glaucoma Surgery in 1 Eye. Issue 3 (March 2016) - Kaushik, Sushmita; Agarwal, Aniruddha; Kaur, Savleen; Lomi, Neiwete; Raj, Srishti; Pandav, Surinder S.
Abstract : Purpose: To measure the change in intraocular pressure (IOP) of the fellow eye after glaucoma surgery in 1 eye. Patients and Methods: In this prospective interventional study, 71 patients with primary and secondary glaucoma, undergoing glaucoma surgery in 1 eye were included. The IOP in the fellow eye following glaucoma surgery in 1 eye from the first postoperative week till 6 months following surgery was studied. Both normal and glaucomatous fellow eyes were included. IOP change from preoperative IOP levels in the fellow eye was analyzed. Patients treated with acetazolamide preoperatively were analyzed separately. Results: The mean baseline IOP of the operated and fellow eyes was 28.14±9.4 and 16.5±6.1 mm Hg, respectively. IOP of fellow eyes significantly increased compared with baseline at all timepoints ( P <0.001), with a maximum rise 6 weeks postoperatively (4.8±3.3 mm Hg). There was no significant difference in the consensual rise between glaucomatous and nonglaucomatous fellow eyes, or between patients treated with or without acetazolamide before surgery. Regression analysis showed no baseline factor associated with the rise in IOP. By the sixth postoperative month, 24 patients required surgery or needed an increase in medications in the fellow eye for IOP control. Conclusions: Glaucoma surgery in eye is associated with a rise in IOP of the fellow eye, regardless of whether the fellow eye is normal or glaucomatous, or had been previously treated with acetazolamide. Fellow eyes of all patients scheduled for glaucoma surgery require careful monitoring of the IOP.